2015
DOI: 10.1186/s12935-015-0156-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the evidence for targeting FOXO3a in breast cancer: a systematic review

Abstract: BackgroundTumour cells show greater dependency on glycolysis so providing a sufficient and rapid energy supply for fast growth. In many breast cancers, estrogen, progesterone and epidermal growth factor receptor-positive cells proliferate in response to growth factors and growth factor antagonists are a mainstay of treatment. However, triple negative breast cancer (TNBC) cells lack receptor expression, are frequently more aggressive and are resistant to growth factor inhibition. Downstream of growth factor rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 56 publications
4
107
0
Order By: Relevance
“…Fourth, S100A7 is responsible for cell detachment induced-anoikis resistance and tumorigenicity in human oral cancer cells. [20,38] Thus, we speculate that YAP and S100A7 might act as the compensatory function depending on cell microenvironment in well differentiated cervical and glossopharyngeal SCC. When these cells are detached or cultured in high density, the Hippo pathway is activated and nuclear YAP is attenuated, which leads to S100A7 induction in order to perform the similar effects as YAP, such as maintenance of cell survival and/or suppression of cell differentiation.…”
Section: Discussionmentioning
confidence: 94%
“…Fourth, S100A7 is responsible for cell detachment induced-anoikis resistance and tumorigenicity in human oral cancer cells. [20,38] Thus, we speculate that YAP and S100A7 might act as the compensatory function depending on cell microenvironment in well differentiated cervical and glossopharyngeal SCC. When these cells are detached or cultured in high density, the Hippo pathway is activated and nuclear YAP is attenuated, which leads to S100A7 induction in order to perform the similar effects as YAP, such as maintenance of cell survival and/or suppression of cell differentiation.…”
Section: Discussionmentioning
confidence: 94%
“…While PPARc is upstream of many of the effectors that are influenced by BAR, the PPARc agonist rosiglitazone did not recapitulate the effects of BAR on gene expression or prevent loss of metabolic activity. Others have shown that FOXO3a is a target for triterpenoids in cancer [15,37].…”
Section: Discussionmentioning
confidence: 99%
“…A number of existing BC drugs target PI3K/AKT [15]. Although the mechanism for the anticancer activities of BAR are not fully understood, many signaling pathways, including mitochondrial regulation via the KEAP1/Nrf2 pathway and glycolytic regulation via the PI3K/mTOR pathway, have been implicated in the anticancer effects of BAR [16].…”
Section: Introductionmentioning
confidence: 99%
“…In TNBC, metabolic dysregulation is driven by factors such as glutathione S-transferase Pi 1 (GSTP1), forkhead box O 3a (FOXO3a), and EGFR-induced c-Myc (4345). Specifically, c-Myc represses thioredoxin-interacting protein (TXNIP), an inhibitor of glycolytic gene expression and glucose uptake (46).…”
Section: Breast-to-brain Metastasesmentioning
confidence: 99%